2004
DOI: 10.1590/s0034-89102004000500017
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to larva migrans syndromes in squares and public parks of cities in Chile

Abstract: Between November 2001 and December 2002, 600 dog fecal samples were collected in main squares and public parks of 13 cities in Chile, from the extreme north to the extreme south of the country. The samples were processed in the laboratory by centrifugal sedimentation and the Harada-Mori methods. T. canis eggs were found in 12 cities. Detection rates ranged from 1.9 to 12.5% with an average of 5.2%. Seven percent of the samples had eggs and 9.5% had rhabditoid and/or filariform larvae of Ancylostomatidae. Stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
0
8
0
10
Order By: Relevance
“…OR,4.20;CI,). This can be associated with the fact that the infective capacity of the ovum of H. gallinarum and A. galli is progressively reduced when exposed to the adverse effects of environmental conditions (SMITH, 1998;MERCADO et al, 2004). Moreover, elevated soil temperatures have been associated with reduced infectivity of the eggs of H. gallinarum and A. galli (CHRISTENSON et al, 1942;TARBIAT, 2012), while desiccation was considered as detrimental to the viability of the eggs of A. galli (CARDOZO;YAMAMURA, 2004;TARBIAT, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…OR,4.20;CI,). This can be associated with the fact that the infective capacity of the ovum of H. gallinarum and A. galli is progressively reduced when exposed to the adverse effects of environmental conditions (SMITH, 1998;MERCADO et al, 2004). Moreover, elevated soil temperatures have been associated with reduced infectivity of the eggs of H. gallinarum and A. galli (CHRISTENSON et al, 1942;TARBIAT, 2012), while desiccation was considered as detrimental to the viability of the eggs of A. galli (CARDOZO;YAMAMURA, 2004;TARBIAT, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, existen casos reportados en Perú en los cuales no se encontró el antecedente epidemiológico de viajes a zonas endémicas 6,8,9 . Así mismo, en un estudio realizado en Chile para evaluar la presencia de agentes causantes de larva migrans cutánea en muestras de heces caninas, se encontró la presencia de larvas de ancylostomideos en 9,5% de las muestras, en 8 de las 13 ciudades incluidas 14 . Esto puede indicar que algunos países de Sudamérica, a pesar de no ser endémicos de esta parasitosis, pueden tener algunas zonas con riesgo de transmisión de larva migrans cutánea.…”
Section: Discussionunclassified
“…Several studies 4,5,16 have been conducted on soil contamination with eggs, cysts, oocysts, and larvae of zoonotic parasites in public places of leisure, such as squares and parks. In this study, conducted in the squares of Belo Horizonte, we observed the presence of a large number of owned and stray dogs, which may explain the significant amount of feces in the environment.…”
Section: Discussionmentioning
confidence: 99%